Whole genome sequencing reveals footprints of adaptive genetic variation in populations of Eruca sativa - Bajpai, Prabodh Kumar; Harel, Arye; Shafir, Sharoni; Barazani, Oz (Frontiers in Ecology and Evolution, 2022)
Populations of Eruca sativa (Brassicaceae) derived from arid and Mediterranean habitats exhibit ecotypic differentiation. Here, pooled DNA sequencing was used to assess adaptive genome differentiation in the two ecotypes. Differentiated SNP loci were scanned with the empirical FST outlier method and correlated with allele frequencies according to environmental parameters. Genetic diversity values were relatively higher in the pooled arid genome, whereas the pooled Mediterranean genome exhibited stronger directional selection, indicating the impact of climatic conditions on genetic diversity. GO enrichment analysis categorized the annotated differentiated loci according to biological processes, revealing a large set of candidate genes related to abiotic and biotic stress responses. Allelic variation was detected in regulatory elements and coding regions (synonymous and non-synonymous mutations) of genes belonging to different transcription factors and phytohormone signaling, suggesting adaptation to both abiotic and biotic conditions. Furthermore, SNP mutations were also found in genic regions belonging to the synthesis of secondary metabolites, including aliphatic glucosinolates and their hydrolyzed bioactive compounds, among others. The results of this eco-genomic study demonstrate the role of divergent abiotic and biotic selection factors in evolutionary processes leading to adaptive ecotypic differentiation.